Analisis Pembangunan Sumber Daya Manusia di Provinsi Bali Tahun 2011-2014 - Sunarya, I Wayan (Jurnal Aplikasi Manajemen, 2016)
This study aimed to analyze: (1) the effect of Life Expectancy at Birth (LEB) to Human Development Index (HDI) in Bali from 2011 to 2014; (2) the effect of Adult Literacy Rate (ALR) to Human Development Index (HDI) in Bali from 2011 to 2014; (3) the effect Mean Years of Schooling (MYS) to Human Development Index (HDI) in Bali from 2011 to 2014. Secondary data, from article entitled Bali In Figures, which is published once a year, namely from the year 2011-2014 by the Central Statistics Agency of Bali. This study implemented panel data with Fixed Effect Model (FEM) method of Generalized Least Square (GLS). The results showed that the Life Expectancy at Birth (LEB) and Mean Years of Schooling (MYS) has positive and significant effect to Human Development Index (HDI) in Bali from 2011 to 2014. However, Adult Literacy Rate (ALR) doesn't significantlyaffect the Human Development Index (HDI) in Bali from 2011 to 2014.